Martin Hengel's Impact on English-speaking Scholarship - Hurtado, Larry W. 1943- (2008)
Professor Martin Hengel is one of the most widely respected and influential New Testament scholars of the late twentieth century. Though German, he has also been very widely read and influential among English-language scholars, his influence facilitated through the prompt translation of so many of his works. He is also distinguished in having made major contributions to the study of second-temple Judaism as well as the NT and early Christianity.
Keywords: Christianity; christological hymns; Christology; English language; Hellenism; Hellenists; Hengel; Hengel, Martin; Judaism; New Testament scholars; NT chronology; Zealots